2022
DOI: 10.3390/ijms23073655
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin Peptide P31-43 Induces mTOR/NFkβ Activation and Reduces Autophagy: The Role of Lactobacillus paracasei CBA L74 Postbiotc

Abstract: Celiac disease (CD) is an autoimmune disease characterized by an altered immune response stimulated by gliadin peptides that are not digested and cause damage to the intestinal mucosa. The aim of this study was to investigate whether the postbiotic Lactobacillus paracasei (LP) could prevent the action of gliadin peptides on mTOR, autophagy, and the inflammatory response. Most of the experiments performed were conducted on intestinal epithelial cells Caco-2 treated with a peptic-tryptic digest of gliadin (PTG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…By far, several studies have reported the regulation of autophagy by postbiotics. For instance, the culture supernatant of Lacticaseibacillus paracasei induced autophagy in Caco‐2 cells (Conte et al, 2022); postbiotics originated from Limosilactobacillus fermentum mitigated hepatotoxicity by activating autophagy (Dinić et al, 2017). However, few study have explored their role in eliminating pathogens and the underlying mechanism remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…By far, several studies have reported the regulation of autophagy by postbiotics. For instance, the culture supernatant of Lacticaseibacillus paracasei induced autophagy in Caco‐2 cells (Conte et al, 2022); postbiotics originated from Limosilactobacillus fermentum mitigated hepatotoxicity by activating autophagy (Dinić et al, 2017). However, few study have explored their role in eliminating pathogens and the underlying mechanism remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…When mTOR is dephosphorylated, autophagy is induced, whereas the opposite happens when mTOR is phosphorylated ( 9 , 39 ). Therefore, in this study, the effects of gliadin peptides P31-43 and PTG on the autophagy pathway were evaluated in Caco-2 cells ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pH after incubation was ~7. The supernatant (metabiotic) was filtered through a 0.22-mm filter to remove the bacterial bodies ( 9 ). This preparation (metabiotic) without the bacterial bodies was used for the experiments and is referred to as “postbiotic” throughout the text.…”
Section: Methodsmentioning
confidence: 99%
“…Since the cytosolic Ca 2+ level is considered a signal to activate autophagy [ 31 ], we hypothesize that a reduced [Ca 2+ ]i and a low release of Ca 2+ from ER could contribute to accumulate autophagosomes in CD cells treated with THP. Recently, it has been demonstrated that in Caco-2 cells gliadin peptides were able to impair autophagy [ 32 , 33 ]. Therefore, it is possible to speculate that gliadin peptides could exacerbate the CD phenotype regarding defective autophagy.…”
Section: Discussionmentioning
confidence: 99%